General principles of Canadian insurance law - Billingsley, Barbara (LexisNexis Canada, 2020)
Whether you are preparing and arguing insurance cases in court, assessing the enforceability of an insurance contract, or advising clients about their insurance contracts - this book provides the straightforward analysis and valuable insight you need to be at your most effective. This comprehensive publication focuses exclusively on Canadian insurance law general principles, and is now fully updated to take into account the latest developments in case law and insurance regulation.